Longitudinal Cytokine Profile in Patients With Mild to Critical COVID-19 - Ling, Lowell; Chen, Zigui; Lui, Grace; Wong, Chun Kwok; Wong, Wai Tat; Ng, Rita W. Y.; Tso, Eugene Y. K.; Fung, Kitty S. C.; Chan, Veronica; Yeung, Apple C. M.; Hui, David S. C.; Chan, Paul K. S. (Frontiers in Immunology, 2021)
The cytokine release syndrome has been proposed as the driver of inflammation in coronavirus disease 2019 (COVID-19). However, studies on longitudinal cytokine profiles in patients across the whole severity spectrum of COVID-19 are lacking. In this prospective observational study on adult COVID-19 patients admitted to two Hong Kong public hospitals, cytokine profiling was performed on blood samples taken during early phase (within 7 days of symptom onset) and late phase (8 to 12 days of symptom onset). The primary objective was to evaluate the difference in early and late cytokine profiles among patient groups with different disease severity. The secondary objective was to assess the associations between cytokines and clinical endpoints in critically ill patients. A total of 40 adult patients (mild = 8, moderate = 15, severe/critical = 17) hospitalized with COVID-19 were included in this study. We found 22 cytokines which were correlated with disease severity, as proinflammatory Th1-related cytokines (IL-18, IP-10, MIG and IL-10) and ARDS-associated cytokines (IL-6, MCP-1, IL-1RA and IL-8) were progressively elevated with increasing disease severity. Furthermore, 11 cytokines were consistently different in both early and late phases, including 7 (GRO-α, IL-1RA, IL-6, IL-8, IL-10, IP-10 and MIG) that increased and 4 (FGF-2, IL-5, MDC and MIP-1α) that decreased from mild to severe/critical patients. IL-8, followed by IP-10 and MDC were the best performing early biomarkers to predict disease severity. Among critically ill patients, MCP-1 predicted the duration of mechanical ventilation, highest norepinephrine dose administered and length of intensive care stay.